Aktivitas Antibakteri Ekstrak Etanolik Daun Jeruk (Citrus nobilis, Citrus sinensis, dan Citrus maxima) Terhadap Bakteri Staphylococcus aureus dan Pseudomonas aeruginosa - Ifandari; einstivina nuryandani (MANILKARA: Journal of Bioscience, 2022)
Some bacteria that live on body surfaces such as Staphylococcus aureus and Pseudomonas aeruginosa can be pathogenic to human. These bacteria are known to be resistant to certain antibiotics. Therefore, it is necessary to develop other alternative materials as safe antibacterial agents. One of the natural ingredients that have potential as antibacterial is citrus leaf. The aim of this study was to determine the inhibitory power of citrus leaf extracts from three types of citruses (Citrus nobilis, Citrus sinensis, and Citrus maxima) against the growth of S. aureus and P. aeruginosa bacteria. This study used the paper disk diffusion method with a percentage of 12.5%, 25%, and 50% of the extract dissolved in 2% carboxymethyl cellulose (CMC). The negative control used 2% CMC, while the positive control used the antibiotic ciprofloxacin. The results showed that the antibacterial activity of the three extracts was significantly different from the negative control, but the activity between the three types of citrus leaf extract was not significantly different. C. nobilis leaf extract with a concentration of 50% had antibacterial activity to Staphylococcus aureus relatively higher than the other two citrus leaf extracts, while in P. aeruginosa, the antibacterial activity of C. maxima leaf extract was relatively higher than other citrus leaf extracts. These results indicated that citrus leaves extracts from C. nobilis, C. sinensis, and C. maxima had inhibitory effects on S. aureus and P. aeruginosa growth.